Project Based Learning (PBL) jako obiecujące wyzwanie dla nauczania matematyki - Hilai, Miri (Studia Edukacyjne, 2020)
Mathematics has always presented a challenge, both for teachers and for pupils, all around the world. Teachers of mathematics of all time periods are interested in having their pupils master the mathematical skills and love math. They deliberate on ways of teaching-learning, because of the tremendous gaps in their pupils’ cognitive abilities and their non-uniform abilities to pay attention and to concentrate. It appears that the main solution in the frontal mathematics lessons is offered to the average pupils, but the main goal is to provide a solution for the entire classroom population. Over the years I have searched for different ways beyond frontal and individualized teaching, so that I could provide a solution for populations with different needs in the mathematics lessons. My search for alternative ways derived also from the need to promote the achievements and to boost the motivation, interest, curiosity, and enjoyment in the learning of mathematics. Contemporary research indicates that there is practical innovative learning which is active and involving; it is called project-based learning (PBL). PBL provides a solution for the improvement of the performances in mathematics, for the motivation of the pupils, and for the inspiration of interest and curiosity in and enjoyment from this field of knowledge. From my experience as a teacher in the past and from the reports of my students in the Gordon Academic College for Education in the PBL course, in such teaching a solution is provided for the different populations in the class. The pupils are engaged in learning in practical and realistic projects that are relevant to their lives. They are more active and autonomous, work cooperatively, and develop patterns of behaviour of independence in learning, self-orientation, and self-regulation. These skills and patterns of behaviour are important to their lives as adults and cultivate the six functions of the learner that are derived from the curriculum in Israel: sensory-motor, self-direction in learning and in its management, intrapersonal and interpersonal, cognitive and meta-cognitive.